Enantioselective Cytotoxicity of Chiral Diphosphine Ruthenium(II) Complexes Against Cancer Cells. Issue 33 (5th May 2022) - Lovison, Denise; Alessi, Dario; Allegri, Lorenzo; Baldan, Federica; Ballico, Maurizio; Damante, Giuseppe; Galasso, Marilisa; Guardavaccaro, Daniele; Ruggieri, Silvia; Melchior, Andrea; Veclani, Daniele; Nardon, Chiara; et al.
Abstract: The chiral cationic complex [Ru(η 1 ‐OAc)(CO)(( R, R )‐Skewphos)(phen)]OAc (2 R ), isolated from reaction of [Ru(η 1 ‐OAc)(η 2 ‐OAc)( R, R )‐Skewphos)(CO)] (1 R ) with phen, reacts with NaOPiv and KSAc affording [RuX(CO)(( R, R )‐Skewphos)(phen)]Y (X=Y=OPiv 3 R ; X=SAc, Y=OAc 4 R ). The corresponding enantiomers 2 S ‐4 S have been obtained from 1 S containing ( S, S )‐Skewphos. Reaction of 2 R and 2 S with ( S )‐cysteine and NaPF6 at pH=9 gives the diastereoisomers [Ru(( S )‐Cys)(CO)(PP)(phen)]PF6 (PP=( R, R )‐Skewphos 2 R ‐Cys; ( S, S )‐Skewphos 2 S ‐Cys). The DFT energetic profile for 2 R with ( S )‐cysteine in H2 O indicates that aquo and hydroxo species are involved in formation of 2 R ‐Cys. The stability of the ruthenium complexes in 0.9 % w/v NaCl solution, PBS and complete DMEM medium, as well as their n ‐octanol/water partition coefficient (logP), have been evaluated. The chiral complexes show high cytotoxic activity against SW1736, 8505 C, HCT‐116 and A549 cell lines with EC50 values of 2.8–0.04  μ M. The ( R, R )‐Skewphos derivatives show higher cytotoxicity compared to their enantiomers, 4 R (EC50 =0.04  μ M) being 14 times more cytotoxic than 4 S against the anaplastic thyroid cancer 8505 C cell line. Abstract : The chiral cationic diphosphine ruthenium(II) complexes [RuX(CO)(PP)(phen)]Y (X, Y=carboxylates, thioacetate, PP=( R, R )‐ or ( S, S )‐Skewphos), isolated as single stereoisomers, inhibit cancer cell proliferation and colonization with EC50 values ranging from 2.8 to 0.04  μ M, the ( R, R )‐enantiomers being up to 14 times more active than the ( S, S) ones. In water, the ( S )‐cysteine and GSH adducts are easily formed from the carboxylate derivatives via aquo complexes.